Inattentional Blindness Increased with Augmented Reality Surgical Navigation. Issue 5 (September 2014) - Dixon, Benjamin J.; Daly, Michael J.; Chan, Harley H.L.; Vescan, Allan; Witterick, Ian J.; Irish, Jonathan C.
Background: Augmented reality (AR) surgical navigation systems, designed to increase accuracy and efficiency, have been shown to negatively impact on attention. We wished to assess the effect "head-up" AR displays have on attention, efficiency, and accuracy, while performing a surgical task, compared with the same information being presented on a submonitor (SM). Methods: Fifty experienced otolaryngology surgeons (n = 42) and senior otolaryngology trainees (n = 8) performed an endoscopic surgical navigation exercise on a predissected cadaveric model. Computed tomography-generated anatomic contours were fused with the endoscopic image to provide an AR view. Subjects were randomized to perform the task with a standard endoscopic monitor with the AR navigation displayed on an SM or with AR as a single display. Accuracy, task completion time, and the recognition of unexpected findings (a foreign body and a critical complication) were recorded. Results: Recognition of the foreign body was significantly better in the SM group (15/25 [60%]) compared with the AR alone group (8/25 [32%]; p = 0.02). There was no significant difference in task completion time (p = 0.83) or accuracy (p = 0.78) between the two groups. Conclusion: Providing identical surgical navigation on a SM, rather than on a single head-up display, reduced the level of inattentional blindness as measured by detection of unexpected findings. These gains were achieved without any measurable impact on efficiency or accuracy. AR displays may distract the user and we caution injudicious adoption of this technology for medical procedures.